Developing software for compiling electronic inflectional dictionary of the Spanish language - Kupriianov, Ye. (ХНУРЕ, 2023)
The paper focuses on the technology of creating software for compiling an electronic inflectional Spanish dictionary using the framework of the L-systems theory by V.A. Shirokov. On its basis all Spanish words were classified into respective paradigmatic types, groups and classes is made, a formal model of the dictionary is built, and the structure of the database and the interface of the virtual lexicographic laboratory to work with the dictionary database are determined. The interface offers a number of functions, including adding, editing, and deleting words and paradigmatic classes. The developed database structure and data editing software tools contribute to the efficient organization of the process of creating a word-based Spanish dictionary. The created database can be successfully used in the study of inflection processes and phenomena. Стаття присвячена технології створення програмного забезпечення для укладання електронного словозмінного словника іспанської мови з використанням апарату теорії Л-систем В.А. Широкова. На її основі вироблено словозмінну класифікацію іспанських мовних одиниць за парадигматичними типами, групами і класами, побудовано формальну модель словника, а також визначено структуру бази даних та інтерфейс віртуальної лексикографічної лабораторії для роботи з базою даних словника. Інтерфейс пропонує низку функцій, зокрема додавання, редагування та вилучення слів та парадигматичних класів. Розроблена структура бази даних та програмні засоби редагування даних сприяють ефективній організації процес створення словозмінного словника іспанської мови. Створена база даних може успішно використовуватись при дослідженні словозмінних процесів і явищ.
Keywords: l-system; lexicographic database; virtual lexicographic laboratory; formal model; л-система; лексикографічна база даних; віртуальна лексикографічна лабораторія; формальна модель